Heat Absorption On Walls With Red Brick Material - Muchlis Alahudin; Anton Topan; Yosi Valentina Simorangkir; Henry Soleman Raubaba (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Merauke is one of the cities in the tropics, has a relatively high temperature. Currently, development in Merauke is quite rapid, so the need for materials, especially wall materials, is much needed. The material that is quite familiar for walls is red stone, however, in the last 2 years in Merauke, a new material for walls has been light stone. In this study, the material of the red stone wall is the main variable, the material is selected and measured to have the ability to absorb heat and emit heat. The methods used in this study were: making a wall prototype (test wall) with red stone material, research using a Thermometer Gun, measurements were taken from 6.00 – 20.00 WIT. The purpose of this study was to determine the effect of the sun’s heat on the redstone walls which included: Peak temperature height and the difference between plastered and unplastered redstone walls, in addition to the thermal properties of the material. On the test wall that was not plastered, the temperature was quite high, reaching 46.1ºC during the day, at measuring point A1 (west side) it was found at the end of the measurement (20.00 WIT) the temperature reached 30.7ºC but on the reverse side of the measuring point B4, the temperature actually reached 32.2ºC (the 2 measuring points were wall pairs without plastering. It was concluded that the measurement results on the west side had a higher temperature, because it was exposed to the sun’s heat for a longer time, we can be sure that the heat temperature was reaching the inside side of the room. The walls the plastered test has a fairly high temperature, reaching 50.7ºC during the day, the difference at the end of the measurement (20.00 WIT) between measuring point A4 and measuring point B1 is very low, namely; at measuring point A4 the temperature reaches 33.8ºC while measuring point B1 reaches a temperature of 33.5ºC.